N-Hexyl-3-(4-hy-droxy-3,5-dimeth-oxy-phen-yl)propanamide - Andrade, L. C. R. (2012)
In the title compound, C(17)H(27)NO(4), which is an hydro-sinapic acid derivative with increased lipophilicity conferred by an additional alkyl chain, the central and the hexyl linear chains contain slightly shorter bond lengths [C-N = 1.316 (2) Å; average linear chain C-C = 1.487 (6) Å] than reported average values [Csp(2)-N = 1.334, C-C for CH(2)-CH(2) = 1.524 and 1.513 Å for CH(2)-CH(3)]. The 4-hy-droxy-3,5-dimeth-oxy-phenyl plane [r.m.s. deviation 0.055 (12) Å] makes an angle of 59.89 (5)° with the central plane of the mol-ecule (composed of the N atom, the carbonyl group and the two methyl-ene C atoms linking the carbonyl group and the ring, [r.m.s. deviation 0.0026 (10) Å], which, in turn, makes an angle of 64.24 (13)° with the essentially planar hexyl chain [r.m.s. deviation 0.035 (18) Å]. The N-H group of the amide group is involved in a bifurcated hydrogen bond towards the hy-droxy and one of the meth-oxy O atoms of the 4-hy-droxy-3,5-dimeth-oxy-phenyl substituent of a neighbouring mol-ecule, forming a two-dimensional network in the (100) plane. In addition, the same hy-droxy group acts as a donor towards the carbonyl O atom of another neighbouring mol-ecule, forming chains running along the b axis.